International Scientific Conference »Research and Education in Nursing«: Book of Abstracts, June 5th 2025, Maribor, Slovenia (University of Maribor Press, 2025)
University of Maribor Faculty of Health Sciences is organising the lnternational Scientific Conference "Research and Education in Nursing". It will be held on June 5th 2024 in Maribor and will include the most recent findings of domestic and foreign researchers in nursing and other healthcare fields. The conference aims to explore advances in nursing and health care research as well as research-based education, in the Slovenian and international arena. Furthermore, it will provide an opportunity far practitioners and educators to exchange research evidence, models of best practice and innovative ideas.